Uma voz libertária na revista Careta: Domingos Ribeiro Filho e a crônica como literatura útil: A libertarian voice in the Careta Magazine: Domingos Ribeiro Filho and the chronicle as useful literature (Revista de História da UEG (REVHIST), 2020)
Abstract: The present article approaches the libertarian literature produced by Domingos Ribeiro Filho (1875-1942) at the humoristic magazine Careta. This writer, although having produced texts to the libertarian and operarian press and to the great press, has a wide literarian work that integrates novels, tales, theatrical critical, chronicles and other types of texts. His collaboration at the Careta magazine as its articulist and later as it´s editor has also been varied and extensive. In lots of his writings published in the magazine it can be perceived critical to the politics and to the behaviors of the epoch, like an alignment with libertarian ideals and projections of more free forms of living.Keywords: Libertarian literature. Careta magazine. Chronicle. Domingos Ribeiro Filho.